Impact of COVID-19 vaccination status on hospitalization and disease severity: A descriptive study in Nagasaki Prefecture, Japan - Guoxi Cai; Shiwen Liu; Yixiao Lu; Yumika Takaki; Fumiaki Matsumoto; Akira Yoshikawa; Toshitsugu Taguri; Jianfen Xie; Kazuhiko Arima; Satoshi Mizukami; Jiwen Wu; Taro Yamamoto; et al. (Human Vaccines & Immunotherapeutics, 2024)
ABSTRACTCoronavirus disease 2019 (COVID-19) was extraordinarily harmful, with high rates of infection and hospitalization. This study aimed to evaluate the impact of COVID-19 vaccination status and other factors on hospitalization and disease severity, using data from Nagasaki Prefecture, Japan. Confirmed cases of COVID-19 infection with vaccination status were included and the differences in characteristics between different vaccination statuses, hospitalization or not, and patients with varying levels of disease severity were analyzed. Furthermore, logistic regression was used to calculate odds ratio (ORs) and 95% confidence intervals (CI) to evaluate the association of various factors with hospitalization and disease severity. From March 14, 2020 to August 31, 2022, 23,139 patients were unvaccinated 13,668 vaccinated the primary program with one or two doses, and 4,575 completed the booster. Vaccination reduced the risk of hospitalization with an odd ratio of 0.759 (95% CI: 0.654–0.881) and the protective effect of completed booster vaccination was more pronounced (OR: 0.261, 95% CI: 0.207–0.328). Similarly, vaccination significantly reduced the risk of disease severity (vaccinated primary program: OR: 0.191, 95% CI: 0.160–0.228; completed booster vaccination: OR: 0.129, 95% CI: 0.099–0.169). Overall, unvaccinated, male, elderly, immunocompromised, obese, and patients with other severe illness factors were all risk factors for COVID-19-related hospitalization and disease severity. Vaccination was associated with a decreased risk of hospitalization and disease severity, and highlighted the benefits of completing booster.